Qualitative assessment of riparian vegetation and management options for flood mitigation in The Satui River, South Kalimantan - Rahman Hakim; Tigor Wilfritz Soaduon Panjaitan (Jurnal Arsitektur Lansekap, 2026)
The Satui River in South Kalimantan, Indonesia, faces significant riparian landscape degradation due to settlements, erosion, and land-use changes, which have intensified flood and landslide risks. This study provides an exploratory assessment of the current ecological functions of the riparian landscape of the river and identifies potential strategies for flood risk mitigation. An exploratory, descriptive qualitative approach was employed, involving field surveys to evaluate the existing vegetation and a literature review of local management plans. Due to the current lack of detailed quantitative data, management strategies and vegetation effectiveness were evaluated using a qualitative rating scale of high (H), medium (M), and low (L) based on technical effectiveness, sustainability, and community adaptation criteria. Field observations revealed that the existing vegetation is dominated by fruit trees and shallow-rooted plants, such as Mangifera indica and Musa paradisiaca, which offer limited riverbank stabilization and habitat support. Qualitative analysis suggests that integrated strategies—combining watershed-scale conservation, riparian corridor restoration, and selective structural measures— should be prioritized for sustainable risk reduction over isolated hard-engineering solutions. Specific recommendations include implementing nature-based solutions, such as vetiver (Chrysopogon zizanioides) for edge reinforcement, reforestation of the upper watershed, and adaptive management involving local communities. While these strategies show high potential in a qualitative framework, the study notes that empirical data on the effectiveness of nature-based solutions in humid tropical regions remain limited, highlighting the need for further quantitative research and pilot projects to validate these findings.